PENGARUH MODAL DAN HASIL PRODUKSI GABAH TERHADAP PENINGKATAN PENDAPATAN PETANI DI KECAMATAN BANDA MULIA KABUPATEN ACEH TAMIANG - nurjanah, nurjanah (AL-IQTISHAD: Jurnal Ekonomi, 2024)
The purpose of this study was to determine the effect of capital and grain yield on increasing farmers income in Banda Mulia District, Aceh Tamiang Regency. The population in this study were all grain farmers in the district Banda Mulia, while the sample taken was 96 farmers with sampling through simple random sampling method. Method of collecting data through questionnaires.The data analysis technique used is multiple linier regression analysis with the calculation of SPSS software. The results showed that the variable capital had a positive and significant effect on the increase in farmer income (with a t count of 2,217and a sig. value of 0,029) and the grain yield variable had a positive and significant effect on the increase in farmer income (with a t count of 5,870 and a sig. value of 0,000).Â  While the variables of capital and productions yields together have a positive and significant effect on the increase in farmer income in Banda Mulia District (with a FÂ  count of 280,953 and a sig. value of 0,000).